PERAN INTELLECTUAL CAPITAL DISCLOSURE SEBAGAI PEMODARSI PENGARUH PERATAAN LABA,CORPORATE GOVERNANCE,KESEMPATAN BERTUMBUH,PERSISTENSI LABA DAN LEVERAGETERHADAP KEINFORMATIFAN LABA - Medy Nisrina M; Vinola Herawaty (Universitas Mercu Buana, 2016)
The purpose of this research is to determine the influence of income smoothing, corporate governance, growth opportunity, earnings persistence and leverage on market response with intellectual capital disclosure as moderating variable. The independent variables in this model are income smoothing, corporate governance, growth opportunity, earnings persistence and leverage. The dependent variable is earnings informativeness as measured by earnings response coefficient. The moderating variable is intellectual capital disclosure. This research also uses control variables which are firm size and profitability. Data for this research were obtained by the company's financial statement and annual report and the Indonesia Stock Exchange’s homepage. Sample that used in this research are 101 manufacturing companies that listed on the Indonesia Stock Exchange for the period 2012-2014. The sampling technique used was purposive sampling method. This research uses multiple regression analysis. An analytical tool that used to analyze the hypothesis is SPSS 21.The result is corporate governance and growth opportunity have positive influences to earnings response coefficient. Leverage has negative influence to earnings response coefficient. Income smoothing and earnings persistence doesn’t have any influence to earnings response coefficient. Intellectual capital disclosure can strengthen a positive relationship between corporate governance and earnings response coefficient. Intellectual capital disclosure can strengthen a positive relation between growth opportunity and earnings response coefficient. Intellectual capital disclosure may strengthen a negative relation between leverage and earnings response coefficient. However, Intellectual capital disclosure can not moderate the relation of income smoothing and earnings persistence against earnings response coefficient. It is proven that profitability as a control variable gives positive influence to earnings response coefficient while Firm size doesn’t have any influence on earnings response coefficient. Keywords : Income Smoothing, Corporate Governance, Growth Opportunity, Earnings Persistence, Leverage, Earnings Response Coefficient, Intellectual Capital Disclosure, Firm Size, Profitability.